Supervision of Unsafe Act on Formwork Workers at Project â€œXâ€ Bekasi City (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Former observation results at â€œXâ€ Project find several unsafe behaviors such as not using personal protective equipment (PPE), smoking and jesting while working. The aim of the study is to determine the association between supervision and unsafe behavior in formwork workers of â€œXâ€ project Bekasi City. This study used cross sectional design. Independent variable was supervision, whereas dependent variable was unsafe behavior. Study population involved all of the formwork workers (40 people). Data was collected through observation using guided checklist on JSA and interview using valid and reliable questionnaire. Data analysis was conducted by chi-square. The study results showed that 25 respondents (62.5%) say that supervision are lacking while 21 respondents (50.2%) perform unsafe behavior. P-value of 0.011 means that there is an association between supervision and unsafe behavior, while the prevalence ratio value of 2.550 with 95%CI of 1,056â€“6,155 imply that poor supervision has 2.550 higher risk on the occurrence of unsafe behavior in workers compared to better supervision. In conclusion, there is an association between supervision and unsafe behavior.